ANALISIS PROSES REKRUTMEN DAN SELEKSI TERHADAP KINERJA KARYAWAN PT. BANK MANDIRI - Delfi Yandri; Nadhifa Putri Adiani (ITB Swadharma, 2020)
In the management of Human Resources (HR), one of the important things is the recruitment and selection process, where this process is expected to assist the company in obtaining qualified and qualified candidates in accordance with the specified qualifications to encourage the achievement of the company goals. Recruitment is the process of finding and attracting prospective employees (applicants) who are able to apply as employees or open job vacancies until they get the desired candidate or meet the qualifications according to the position or vacancy available. Selection is the first attempt by the company to obtain qualified employees. and competent who will serve and do all the work in the company. Selection is a material part of human resource management operations, namely procurement, while the procurement itself consists of planning, recruitment, selection, placement, and production. The purpose of this study was to determine the recruitment and selection process on employee performance at PT. Bank Mandiri